Analysis of Urban Form Dynamics in The Suburbs of Surakarta City 2013-2023 - Istiyanti Nur Marfu'ah; Rita Novani; Pipit Wijayanti; Siti Azizah Susilawati (Department of Geography Education, University of Jember, 2024)
Urban Form has become necessary for city planning management to see the sustainability of a city. A better understanding of different urban forms is imperative to facilitate the evolution of cities towards a more sustainable urban development trajectory in the future. The study aims to analyze the dynamics of urban form and the changes in land cover within the peri-urban area of Surakarta City, which is directly influenced by the development of Surakarta City. The analysis was conducted from a landscape ecology perspective, employing a spatial metrics approach at the landscape level to assess the dynamics of urban form using quantitative descriptive, including a spatial approach. A similar approach was adopted at the class level in order to examine the dynamics of land cover changes. The results of the image analysis were validated using the Kappa index, yielding an image accuracy level of 0.86 (86%). The results of this study show that the urban form in the peri-urban area of Surakarta City tends to move towards a compact urban form. Meanwhile, each land cover, vegetation, and water body become increasingly fragmented, with areas becoming narrower as time passes. Built-up and agricultural land are becoming more compact and concentrated along with development. In conclusion, the dynamics of urban form in the peri-urban area of Surakarta City tends to lead to compact urban form.